USE OF PRESIPITATION METHODS TO REDUCE Cu IN THE LIQUID WASTE INDUSTRY LIQUID IN KOTAGEDE - Chanel Tri Handoko; Tri Budi Yanti; Halimatus Syadiyah; siti marwati (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2013)
This research was to determine the optimal pH decreased level of Cu using precipitation method and effectivity of the reduction Cu metal level using lime solution as precipitatingagent. The research was conducted by collecting the silver industrial wastewater samples from 3 different places, analyzing the initial Cu level, precipitation treatment of the sample, and analyzing the Cu level after precipitation process. Precipitation process was done by reacting the waste water sample and a solution of Ca(OH)2 0.2 M at pH variation of 7, 8, 9, 10, and 11, then allowed to settle for 24 hours. Then the optimal pH of the experiment was used as a pH in the precipitation process using 5% lime solution. Analysis of the Cu metal level in this study was using AAS instrument. Sample C has pH value =10.3 (alkaline), so no further precipitation process is carried out on sample C. Optimal pH precipitation to decresase Cu level is 8. Cu level after treatment precipitation using 5% lime solution at pH 8 is 0.6583 ppm for sample A and 0.4697 ppm for sample B. When compared with the initial Cu level it is 28132.7430 ppm for sample A and 11233.467 ppm for sample B, the precipitation method using lime solution effective to reduce Cu level.